Accelerated 4D self‐gated MRI of tibiofemoral kinematics. (5th September 2017) - Mazzoli, Valentina; Schoormans, Jasper; Froeling, Martijn; Sprengers, Andre M.; Coolen, Bram F.; Verdonschot, Nico; Strijkers, Gustav J.; Nederveen, Aart J.
Abstract : Anatomical (static) magnetic resonance imaging (MRI) is the most useful imaging technique for the evaluation and assessment of internal derangement of the knee, but does not provide dynamic information and does not allow the study of the interaction of the different tissues during motion. As knee pain is often only experienced during dynamic tasks, the ability to obtain four‐dimensional (4D) images of the knee during motion could improve the diagnosis and provide a deeper understanding of the knee joint. In this work, we present a novel approach for dynamic, high‐resolution, 4D imaging of the freely moving knee without the need for external triggering. The dominant knee of five healthy volunteers was scanned during a flexion/extension task. To evaluate the effects of non‐uniform motion and poor coordination skills on the quality of the reconstructed images, we performed a comparison between fully free movement and movement instructed by a visual cue. The trigger signal for self‐gating was extracted using principal component analysis (PCA), and the images were reconstructed using a parallel imaging and compressed sensing reconstruction pipeline. The reconstructed 4D movies were scored for image quality and used to derive bone kinematics through image registration. Using our method, we were able to obtain 4D high‐resolution movies of the knee without the need for external triggering hardware. The movies obtained with and without instruction did not differ significantly in terms of image scoring and quantitative values for tibiofemoral kinematics. Our method showed to be robust for the extraction of the self‐gating signal even for uninstructed motion. This can make the technique suitable for patients who, as a result of pain, may find it difficult to comply exactly with instructions. Furthermore, bone kinematics can be derived from accelerated MRI without the need for additional hardware for triggering. Abstract : In this study, we developed a method to obtain four‐dimensional (4D) imaging of the human knee during active flexion/extension motion, without the use of an external gating system. The method, based on a stack‐of‐stars acquisition, was tested for instructed and uninstructed motion tasks, and shown to be robust against imperfections in the execution of the motion task. This technique could also make dynamic imaging suitable for patients who, as a result of pain, may find it difficult to comply exactly with motion instructions.